2016
DOI: 10.11648/j.js.s.2016040301.13
|View full text |Cite
|
Sign up to set email alerts
|

Response of Post-Mastectomy Lymphedema to Extracorporeal Shockwave Therapy

Abstract: Introduction: Post-mastectomy lymphedema is a chronic, debilitating disorder that is frequently misdiagnosed, treated too late or not treated at all, Lymphedema (LE) is an abnormal accumulation of protein-rich fluid in the interstitium leading to limb swelling, chronic inflammation and reactive fibrosis of the affected tissues resulting from damage to lymphatic circulation following surgery, chemotherapy and/or radiation therapy. The aim was to investigate the effect of shockwave therapy on the post-mastectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
10
2
Order By: Relevance
“…Therefore we tried to provide an alternative noninvasive method for treating the residual LE. The mean value of pre-treatment total volume of the upper limb in our patient group was 3086.4 mL, this was more important compared with 2332.9 mL in the study of Bae and Kim, 21 and only 1219.33 mL in the study of El-Shazly et al 24 They even excluded subjects with a total arm circumference difference of 8 cm. No absolute values of affected arm volume are reported by Mahran and Thabet, 22 Cebicci et al 23 or Abdelhalim and Samhan.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Therefore we tried to provide an alternative noninvasive method for treating the residual LE. The mean value of pre-treatment total volume of the upper limb in our patient group was 3086.4 mL, this was more important compared with 2332.9 mL in the study of Bae and Kim, 21 and only 1219.33 mL in the study of El-Shazly et al 24 They even excluded subjects with a total arm circumference difference of 8 cm. No absolute values of affected arm volume are reported by Mahran and Thabet, 22 Cebicci et al 23 or Abdelhalim and Samhan.…”
Section: Discussioncontrasting
confidence: 51%
“…In the pilot study of Cebicci et al 23 265.9 mL reduction was reported after 4 weeks of ESWT, this result was maintained after 6 months. El-Shazly et al 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective treatment of lymphedema in patients with breast cancer is of great importance and can enhance their quality of life [14,15]. Several studies have reported more improvement following combined techniques [16][17][18][19]. Koo et al reported a more significant improvement after combination of heperbaric oxygen therapy with CDT in patients with BCRL [17].…”
Section: Introductionmentioning
confidence: 99%
“…107 apy (ESWT) was also found to be effective for 108 lymphoedema volume reduction both post treatment 109[40,41] and at 6 month follow-up[41].110 6. Self-treatment including weight loss 111 Life-long self-management is necessary to con-112 trol lymphoedema and is essential for achieving 113 and maintaining successful treatment, as the dam-114…”
mentioning
confidence: 99%